Learning Strategies Used By The Students In Reading Class At SMP N 1 Kebakkramat In 2016/2017 Academic Year - Choiriyah, Anna Eri; , Nur Hidayat, M.Pd (2016)
This research is about learning strategies used by the students in reading class at SMP N 1 Kebakkramat in 2016/2017 Academic Year. The objectives of this research are to know the learning strategies used by the students of VIIIF class of SMP N 1 Kebakkramat in learning reading and to know the effects of various learning strategies used by the students on the English achievement. The type of this research is descriptive qualitative research. The method of collecting data in this research are observation, interview, and document. The result of this research shows that the students used metacognitive, cognitive, and socio-affective strategies based on O'Malley and Chamot in learning reading. Student who have high score applies twelve learning strategies, student who have middle score applies seven learning strategies, and students who have low score applies four learning strategies. The results also shows that by using various learning strategies, the students gets some effects such as made learning became an enjoyable activity, being an effective students, and getting the good score.